Special plan of action in situations of warning and eventual droughts of the Tagus river basin - Soriano Roncero C.M.; Garrote L. (Drought management: scientific and technological innovations, 2008)
In accordance with Article 27 of the Spanish Law 10/2001, where the National Hydrologic Plan is passed, the Spanish Tagus River Basin Water Organism devised, during the period of 2005-2007, the Special Plan of Action in Situations of Warning and Eventual Drought of the Tagus River Basin (Special Drought Plan- SDP). The main objective of this SDP of the Tagus Basin is the specification of measures of control, risk assessment, organization of decision making and implementation of mitigation measures which are required to minimize the frequency and intensity of water shortage conditions, and to reduce the environmental and socioeconomic effects of these extreme situations.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)